2020
DOI: 10.1002/1873-3468.13809
|View full text |Cite
|
Sign up to set email alerts
|

RecJ from Bacillus halodurans possesses endonuclease activity at moderate temperature

Abstract: RecJ homologs, which occur in virtually all prokaryotes and eukaryotes, play key roles in DNA damage repair and recombination. Current evidence shows that RecJ family proteins exhibit exonuclease activity, degrading single‐stranded nucleic acids. Here, we report a novel RecJ isolated from Bacillus halodurans, which utilizes double‐stranded DNA as a substrate and functions as an endonuclease. Bacillus halodurans RecJ (BhRecJ) cleaves supercoiled plasmids into open circular and linear forms. Besides the typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Unlike typical members of the GdpP family, such as B. subtilis GdpP, MbovGdpP is only characterized by a GGDEF-like motif and a DHH-DHHA1 domain, but no PAS motif ( Figure 1 ). Yet, sequence comparison with other members of the DHH superfamily revealed similarity with prokaryotic subfamily I members including cyclic nucleotide phosphodiesterase, nanoRNases, and exonuclease RecJ ( Srivastav et al, 2019 ; Wang et al, 2020 ). In particular, MbovGdpP sequence alignment with RecJ and RecJ-like proteins revealed an important level of similarity ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike typical members of the GdpP family, such as B. subtilis GdpP, MbovGdpP is only characterized by a GGDEF-like motif and a DHH-DHHA1 domain, but no PAS motif ( Figure 1 ). Yet, sequence comparison with other members of the DHH superfamily revealed similarity with prokaryotic subfamily I members including cyclic nucleotide phosphodiesterase, nanoRNases, and exonuclease RecJ ( Srivastav et al, 2019 ; Wang et al, 2020 ). In particular, MbovGdpP sequence alignment with RecJ and RecJ-like proteins revealed an important level of similarity ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A novel class of RecJ nucleases, distinct from the classic RecJ nucleases and derived from Bacillus alcalophilus, Bacillus cereus, and Bacillus halodurans, exhibit not only the exonuclease activity of RecJ but also endonuclease activity (Ma et al, 2021;Wang et al, 2020;Zheng et al, 2020;Srivastav et al, 2019;Makarova et al, 2012). Based on the combined exo-and endonuclease activities of the RecJ (BaRecJ) nuclease from B. alkaliphilic, we established a novel global in vivo mutagenesis method, differentiating it from current global in vivo mutagenesis mechanisms (Luan et al, 2013;Badran and Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…RecJ enzymes function in DNA repair and recombination, nucleotide recycling, stress tolerance, and the final stages of chromosome duplication ( 28 - 33 ). In bacteria, such as Escherichia coli , RecJ is a single-stranded (ss) DNA-specific 5′−3′ exonuclease that is processive ( 26 , 27 ), while other bacterial RecJ enzymes are identified that cleave dsDNA ( 34 ). Archaea have an expanded repertoire of RecJ homologs related to bacterial RecJ and eukaryal Cdc45, the latter a non-catalytic subunit of the CMG complex.…”
Section: Introductionmentioning
confidence: 99%